Induced Pluripotent Stem Cell-Derived Monocytes/Macrophages in Autoinflammatory Diseases - Tanaka, Takayuki; Shiba, Takeshi; Honda, Yoshitaka; Izawa, Kazushi; Yasumi, Takahiro; Saito, Megumu K.; Nishikomori, Ryuta (Frontiers in Immunology, 2022)
The concept of autoinflammation, first proposed in 1999, refers to a seemingly unprovoked episode of sterile inflammation manifesting as unexplained fever, skin rashes, and arthralgia. Autoinflammatory diseases are caused mainly by hereditary abnormalities of innate immunity, without production of autoantibodies or autoreactive T cells. The revolutionary discovery of induced pluripotent stem cells (iPSCs), whereby a patient’s somatic cells can be reprogrammed into an embryonic pluripotent state by forced expression of a defined set of transcription factors, has the transformative potential to enable in vitro disease modeling and drug candidate screening, as well as providing a resource for cell replacement therapy. Recent reports demonstrate that recapitulating a disease phenotype in vitro is feasible for numerous monogenic diseases, including autoinflammatory diseases. In this review, we provide a comprehensive overview of current advances in research into autoinflammatory diseases involving iPSC-derived monocytes/macrophages. This review may aid in planning of new studies of autoinflammatory diseases.